PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK JIGSAW UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR - N Yohana (Jurnal Pendidikan Ekonomi Indonesia, 2022)
This study aims to determine and obtain an overview of the application of the jigsaw technique cooperative learning model to increase motivation and learning outcomes in economics subjects in class X IPA 5 SMA N 1 Dukupuntang, Cirebon Regency. The method used by the Classroom Action Research Model that will be used in this research is the Kemmis and McTaggart model. The research subjects were students of class X IPA 5 SMAN 1 Dukupuntang Cirebon Regency with a total of 36 students consisting of 10 male students and 26 female students. The conclusion of this research is that the application of the jigsaw technique of cooperative learning model has a great influence on Students' Motivation And Learning Outcomes In Economics Subjects